18F-Fluorcholine-PET/CT for localizing hyperfunctioning parathyroid glands and optimizing surgical treatment in patients with hyperparathyroidism. (28th May 2021) - Gass, J -M; Wicke, C; Henzen, C; Mona, C; Strobel, K; Metzger, J; Suter, I; Müller, W; Fischli, S
Abstract: Objective: Hyperparathyroidism (HPT) is a common endocrine disorder. Definitive cure can only be reached by surgical removal of all diseased glands. The surgical strategy and management continue to evolve. Exact preoperative localization of hyperfunctioning glands is of paramount importance to prevent unnecessary surgical exploration. Unfortunately, the number of false negative or inconclusive results in standard imaging techniques is rather high. The aim of this study is to evaluate the diagnostic accuracy of 18F-Fluorcholine-PET/CT (FCH-PET/CT) and its sensitivity in a large cohort of patients with primary as well as secondary/tertiary and familial HPT with negative and/or discordant findings in ultrasound and/or 99mTc-sestamibi scintigraphy/SPECT/CT. Methods: Between 2015 and 2020 96 patients with HPT and negative/equivocal conventional imaging were referred for FCH-PET/CT. 69 patients who have undergone surgery and histopathologic workup were analyzed in this retrospective single institution study. 60 patients suffered from primary HPT, 4 from secondary or tertiary HPT and 5 from familial HPT. Sensitivities, positive predictive values, and accuracies were calculated. Results: All patients showed normalized serum calcium levels in the direct postoperative period. 50 of 60 patients (8 results are awaited) with primary HPT and 4 of 4 patients with secondary/tertiary HPT showed normal calcium levels after 6 months and were cured. 4 of 5 patients with familial HPT were cured as well while 1 patient deceased before 6 month follow up. Sensitivity per lesion for primary HPT was 88%, for secondary/tertiary HPT 75% and for familial HPT 75%, respectively. Sensitivity per patient was 92% for primary HPT, 100% for secondary/tertiary HPT and 50% for familial HPT, respectively. Positive predictive value was 98% in primary HPT and 100% in secondary/tertiary HPT and 100% in familial HPT as well. Conclusion: Diagnostic accuracy of 18F-Fluorcholine-PET/CT for patients with primary as well as secondary/tertiary and familial hyperparathyreoidism ist excellent . 18F-Fluorcholine-PET/CT is a valuable tool for endocrine surgeons to optimize the surgical treatment of patients with hyperparathyroidism.